Imaging of Noncalcified Ductal Carcinoma In Situ - Bragg, Ashley; Candelaria, Rosalind; Adrada, Beatriz; Huang, Monica; Rauch, Gaiane; Santiago, Lumarie; Scoggins, Marion; Whitman, Gary (Journal of Clinical Imaging Science)
Ductal carcinoma in situ (DCIS) is a commonly encountered malignancy, accounting for approximately 20% of new breast cancer diagnoses in the United States. DCIS is characterized by a proliferation of tumor cells within the terminal duct lobular unit with preservation of the basement membrane. Typically nonpalpable and asymptomatic, DCIS is most often detected as calcifications on screening mammography. However, DCIS may also be noncalcified. When compared to calcified DCIS, noncalcified DCIS is more likely to be symptomatic, with patients most often presenting with nipple discharge or a palpable mass. Diagnosing noncalcified DCIS is challenging since it may be occult or subtle on mammography, and ultrasound findings can be nonspecific and may be interpreted as benign fibrocystic changes. In cases with a calcified component of DCIS, the extent of DCIS may be underestimated by mammography because not all involved areas may calcify. Breast magnetic resonance imaging (MRI), although less readily available than mammography and ultrasound, is advantageous in detecting noncalcified DCIS, especially high grade DCIS, which may not develop microcalcifications. MRI relies on abnormal contrast uptake due to tumor vascularity and changes in vessel density and permeability. This pictoral review presents the spectrum of imaging findings of noncalcified DCIS to assist radiologists in accurately detecting and describing its key imaging findings. Utilizing different modalities, we review the differential diagnoses for noncalcified DCIS, show illustrative cases of noncalcified DCIS, and discuss the importance of this entity.